Rare bird documentation form for Northern Goshawk at Big Creek State Park, 1984 - Proescholdt, Bethet al (1984)
Rare bird documentation form for a Northern Goshawk at Big Creek State Park in Polk County, IA on March 25, 1984. Epson - sheet feed